A call for wild seed justice - Saleh-Hanna, Viviane (Abolish criminology, 2022)
A reading of Octavia E. Butler’s Wild Seed from her Patternist series and both Parables, inspired and guided by the artwork of abolitionist artist and organizer Dara Kwayera Imani Bayer to form a call for Wild Seed Justice: a call to sketch new worlds for us to grow into, to imagine and create sustainable gardens with abundant, changing, growing pathways to justice so that we can access beauty and freedom instead of continuing to loop back into the repressive colonial thinking of crime, punishment, and rehabilitation. And finally, this is a call to reclaim and rebirth justice beyond the shadows, traps, and delusions of colonialism, and far beyond the limiting and twisting narratives of criminology. What is Wild Seed Justice? It is the abolition of criminology, an absolute end to all the white supremacist, enslaving, arresting, imprisoning, sentencing, and colonizing mythologies/institutions this field has created about and against humanity, society, and justice.